Does Banking in Indonesia tend to be Concentrated? - Maharani, Novita Kusuma; Sumardi, Sumardi; Salisu, Auwal (Universitas Islam Negeri Raden Intan Lampung, 2019)
The banking in Indonesia has undergone several changes in the market structure that ultimately impacts the prevailing policies and regulations. This study aims to examine the impact of changes in the banking market structure identified through the level of market concentration in the banking environment and examine the factors that influence the level of concentration of the banking market from 2005 to 2016. The study also examined the impact of changes in banking structure during the global crisis. The measurement of banking concentration used in this study is the Herfindahl-Hirschman Index (HHI). Furthermore, the influential factors consist of: (1) Bank specification, including bank size (Size), credit risk (NPL), profitability (ROE), banksoundness(CAR),(2)Market specification,namely the number of standingbank (NUM), and (3) Global crisis. The study used GLS (Generalized Least Square) method to detect autocorrelation on each variable.The results show that banks in Indonesia tended to have a low level of market concentration. The results are also in accordance with the SCP paradigm which states that banks tend to generate high profits when the level of banking market concentration is high.Keywords : Market Concentration, Competition, Dual-Banking, Bank Specification, Market Specification, Global Crisis.